1997
DOI: 10.1046/j.1365-3083.1997.d01-409.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody Production in Healthy Elderly People is not Promoted by Interleukin‐10 Although This Cytokine is Expressed in Them by a Peculiar CD8+CD3+ Large Granular Cell Subpopulation

Abstract: Healthy elderly people tend to have autoantibodies in their sera. These antibodies, not being associated with any clinical manifestation, have been considered as natural autoantibodies. In systemic lupus erythematosus, as well as in rheumatoid arthritis, the presence of autoantibodies characteristic of these diseases (anti‐dsDNA and rheumatoid factor, respectively) depends on the endogeneous production of IL‐10. The same could hold true for autoantibodies found in healthy elderly individuals. In the present wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
1
3
0
1
Order By: Relevance
“…Previous studies have reported that IL-10 levels and signaling in skeletal muscle decrease with aging, and those findings are consistent with our current data showing lower IL-10 levels in aging WT mice (11,(29)(30)(31). In contrast, M IL10 mice were protected from this aging-associated effect as muscle IL-10 levels remained consistently higher and within a physiological range.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported that IL-10 levels and signaling in skeletal muscle decrease with aging, and those findings are consistent with our current data showing lower IL-10 levels in aging WT mice (11,(29)(30)(31). In contrast, M IL10 mice were protected from this aging-associated effect as muscle IL-10 levels remained consistently higher and within a physiological range.…”
Section: Discussionsupporting
confidence: 93%
“…Following the SARS-CoV-2 infection and virus entrance, angiotensin-converting enzyme 2 (ACE2)-expressing type II alveolar epithelial cells are the main target of the virus ( 94 , 95 ). However, a wide range of other cells in different organs, such as cholangiocytes in the liver, can express ACE2 and become infected ( 96 ).…”
Section: Immunopathogenesis Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Llorente and colleagues evaluated basal IL-10 production by PBMC cultured for 24 hours without stimulation and showed comparable levels in young and elderly [53]. Stimulation of PBMCs with PHA [Bernstein, et al submitted] or with superantigens TSST [36] or Staphylococcus aureus Cowan (SAC) [43] also demonstrated no age-related differences.…”
Section: Il-iomentioning
confidence: 99%